DETECTION OF Macrobrachium rosenbergii Nodavirus (MrNV) AND EXTRA SMALL VIRUS (XSV) DISEASES ON GIANT FRESHWATER PRAWN, Macrobrachium rosenbergii AT SAMAS, YOGYAKARTA - Isti Koesharyani; Lila Gardenia (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2014)
Mass mortality of giant freshwater prawn (Macrobrachium rosenbergii de Man) in grow-out farmers occurred in early February 2012 at Instalation Coastal of Aquaculture Samas, Bantul, D.I. Yogyakarta. The clinical sign of shrimp was whitish coloration on abdominal and tail muscle. The sympton was the same as in other cases of mortality caused by prawn Macrobrachium rosenbergii nodavirus (MrNV) and Extra Small Virus (XSV). Prawn samples were diagnosed by standard protocols Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) using specific primers and histopathology analysis. The result showed that all samples indicated positive 13/15 the MrNV and 5/15 positive XSV, and there were 4/15 positive samples both (MrNV and XSV). Analysis of histopathology showed that damaged muscle was indicated by the presentation of necrotic tissues with nuclear pyknosis or degeneration of muscle in infected tissues. Based on diagnosis by RT-PCR and histopathological, mass mortality of the giant freshwater prawn in Indonesia is determined to be caused by “white muscle disease (WMD)/white tail disease (WTD)”.